BCL6 interacting corepressor contributes to germinal center T follicular helper cell formation and B cell helper function - Yang, Jessica A. (J Immunol, 2015)
CD4(+) germinal center (GC) T follicular helper (GC-Tfh) cells help B cells become long-lived plasma cells and memory cells. The transcriptional repressor BCL6 plays a key role in GC-Tfh formation by inhibiting the expression of genes that promote differentiation into other lineages. We determined whether BCOR, a component of a Polycomb repressive complex that interacts with the BCL6 BTB domain, influences GC-Tfh differentiation. T cell-targeted BCOR deficiency led to a substantial loss of peptide:MHCII-specific GC-Tfh cells following Listeria monocytogenes infection and a 2-fold decrease following immunization with a peptide in CFA. The reduction in GC-Tfh cells was associated with diminished plasma cell and GC B cell formation. Thus, T cell-expressed BCOR is critical for optimal GC-Tfh differentiation and humoral immunity.